AN INVESTIGATION INTO THE ENTREPRENEURIAL JOURNEY OF AN INDIGENOUS PRODIGY: A CASE STUDY OF AN INDIAN ENTREPRENEUR (Singaporean Journal of Business Economics and Management, 2019)
The present study was taken up to explore entrepreneurial journey of an indigenous entrepreneur in India. The aim was to understand the vision of the entrepreneur, the value preposition offered by the entrepreneur, the entrepreneurial process adopted by the entrepreneur, business model used in the enterprise, role of creativity and innovation in the growth of the enterprise and failure suffered by the entrepreneur and its consequence. The findings of the current study would be an eye opener and a source of inspiration for many who wish to take up entrepreneurship as a career. It would remove several myths about entrepreneurship which discourage people to taken this route. It shall give valuable insights to both existing as well as aspiring entrepreneurs. It would also give insights to the existing family businesses so as how to draw balance between family and business. This study will encourage and motivate many to replicate the business model in their respective regions.